Pengaruh Kompos Bungkil Kopra Terhadap Pertumbuhan Dan Hasil Tanaman Tomat Pada Tanah Podsolik Merah Kuning - yulia, mirnawati (Jurnal Sains Pertanian Equator, 2014)
THE INFLUENCE OF COPRA MEAL COMPOST TO GROWTH AND YIELD OF TOMATO PLANTS ON RED-YELLOW PODZOLIC SOILS Mirnawati Yulia (1), Dini Anggorowati (2), Asnawati (2) (1)Student of Agriculture Faculty (2) Lecturers of Agriculture Faculty Tanjungpura University Pontianak ABSTRACT The purpose of conducting this research was to know the influence of copra meal compost to the growth and yield of tomato plants on red-yellow podzolic soils. The research was done at the Experimental Garden of Agriculture Faculty of Tanjungpura University, Pontianak. It was held from July 10th, 2013 and ended on October 12th, 2013. The research was Completely Randomized Design which consists of 5 treatment and 5 replications, each replication consisted of 4 samples of plants. The treatment given is k1 (690 g/polybag which equivalent to 5% of organic material), k2 (1.433 g/polybag which equivalent to 10% of organic material), k3 (2.177g/polybag which equivalent to 15% of organic material), k4 (2.920 g/polybag which equivalent to 20% of organic material), and k5 (3.664 g/polybag which equivalent to 25% of organic material). The variables that were observed in this research were plant height (cm), chlorophyll leaves (SPAD units), leaf area (cm2), root volume (cm3), top dry weight of plant (g), root dry plant (g), days to flowering (DAP), harvesting (DAP), number of fruits for each plant (fruit), fruit weight for each unit (g), weight for each fruit (g), fruit diameter (cm), and the environment observation. The research finding indicated that copra meal compost could improved the growth and yield of tomato plants on red-yellow podzolic soils. Meanwhile, the efficient dose of copra meal compost to be given to tomato plants was 1.433 g/polybag which equivalent to 10% of organic material. Keywords : red-yellow podzolic soils, tomato, copra meal compost